Pemanfaatan Data Science dalam Meningkatkan Kualitas Pembinaan SDM Militer - Nugroho, Dhanang Ghofur; Johan, Firman; Mufidin, Mufidin (LP. Ma'arif Janggan Magetan, 2023)
In today's digital era, data has become a very valuable asset in decision making in the military field. Where, data science can be used for various purposes, such as risk prediction and analysis, policy development, human resource development, operational efficiency improvement, and predicting someone's length of service in the military. However, effective implementation of data science also requires adequate data infrastructure, strict data security, and skilled and trained human resources in data science. The purpose of this study is to discuss the effect of using data science in developing the quality of human resources, where from this point of view data science is considered to be able to make a significant contribution in increasing the effectiveness and efficiency of military human resources development in Indonesia. This research method is a survey method with the aim of obtaining data on the use and benefits of data science in developing military human resources with a sample of 50 people. As for data processing using SPSS software analysis tools. Utilization of data science is the independent variable in this study, while the quality of military human resource development in Indonesia is the dependent variable, with the control variable being the level of education and experience of military human resources. The results of multiple linear regression tests show that the utilization of data science, education level, and experience of military human resources simultaneously has a significant effect on the quality of military human resource development in Indonesia.